2016
DOI: 10.1016/j.jff.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative properties of 34 green leafy vegetables

Abstract: Green leafy vegetables available in Sri Lanka have not been fully exploited though they are stipulated to be rich sources of natural antioxidant. This study examined the antioxidant properties of thirty four edible green leafy vegetables popular in Sri Lanka. Methanolic extracts of leafy vegetables were analyzed for total phenolic, carotene and chlorophyll content and were evaluated for total antioxidant capacity, reducing power, lipid peroxidation and DPPH radical scavenging assays. The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 52 publications
3
72
3
Order By: Relevance
“…The order of soluble phenolic content of the extracts of leaves varieties was C. auriculata > O. zeylanica > S. grandiflora > P. edulis > G. lactiferum > C. asiatica . Similar observation also reported previously for total phenolic content by Gunathilake and Rupasinghe (). Interestingly, C. asiatica showed higher bound phenolics level and it is comparable with other leafy types, though its soluble phenolic content was three times lower compared with C. auriculata .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The order of soluble phenolic content of the extracts of leaves varieties was C. auriculata > O. zeylanica > S. grandiflora > P. edulis > G. lactiferum > C. asiatica . Similar observation also reported previously for total phenolic content by Gunathilake and Rupasinghe (). Interestingly, C. asiatica showed higher bound phenolics level and it is comparable with other leafy types, though its soluble phenolic content was three times lower compared with C. auriculata .…”
Section: Resultssupporting
confidence: 92%
“…Recent years phenolics and carotenoids compounds have received remarkable attention due to their antioxidant capacities (Deng et al, ; Li, Wong, Cheng, & Chen, ). Green leafy vegetables are considered as rich sources of natural antioxidant vitamins and other bioactive compounds and however, leafy vegetables available in Sri Lanka have not been fully exploited (Gunathilake & Rupasinghe, ). Recently 34 leafy vegetables have been screened for their antioxidant capacities and have reported several leafy vegetables possess good antioxidant properties (Gunathilake & Rupasinghe, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…scavenging singlet molecular oxygen and peroxyl radicals (Stahl & Sies, 2003), and Gunathilake and Ranaweera (2016) have reported that C. asiatica leaves possess antioxidant activities toward free radical scavenging, lipid peroxidation inhibition, and reducing potential.…”
mentioning
confidence: 99%
“…. Leaves of C. asiatica contain polyphenols, carotenoids and possess antioxidant activity(Gunathilake & Ranaweera, 2016;Rahman et al, 2013). Leaves of C. asiatica contain polyphenols, carotenoids and possess antioxidant activity(Gunathilake & Ranaweera, 2016;Rahman et al, 2013).…”
mentioning
confidence: 99%